Recombination and the formation of chiasmata in meiosis - Whitby, Matthew (Henry Stewart Talks, 2009)
The metazoan life cycle, Meiosis vs. mitosis, Mitotic chromosome segregation, Models of homologous recombination and how it generates chiasmata, Initiation of homologous recombination by programmed DNA double-strand breaks, Mechanisms of double-strand break repair, Mechanisms of crossover formation